Suppletivismus als lexikographisches Problem (am Beispiel von allgemeinen einund zweisprachigen Wörterbüchern) - Monika Bielińska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Suppletion is a linguistic phenomenon that is interesting from a linguistic-historical, linguistic-typological and foreign-language-didactic point of view because it concerns very frequently used lexemes. This article deals with suppletion from a lexicographical perspective. The focus is on the treatment of suppletive forms in monolingual and bilingual dictionaries of German and Polish. It examines which lemmatic and non-lemmatic items giving conjugational forms of the verbs sein and być occur in the selected dictionaries. The article attempts to show the connection between the treatment of the suppletive forms and the dictionary functions. It is also emphasized that a holistic analysis of suppletion in dictionaries should encompass many aspects.